Assessment of airborne nanoparticles present in industry of aluminum surface treatments. Issue 3 (4th March 2017) - Santos, R. J.; Vieira, M. T.
ABSTRACT: Conventional industrial processes are emission sources of unintended nanoparticles which are potentially harmful for the environment and human health. The aim of this study is to assess airborne nanoparticle release from aluminum surface treatment processes in various workplaces. Two direct reading instruments, a scanning mobility particle sizer to measure size distribution and a nanoparticle surface area monitoring to measure the surface area of particles deposited in the human lung, were employed to perform area monitoring. The lacquering paint was the process which released the highest concentration of particles from 10–487 nm (7.06 × 10 6 particles/cm 3 ). The lacquering baths process emitted particles of the largest average size (76.9 nm) and the largest surface area deposited in the human lung (167.4 µm 2 /cm 3 ). Conversely, the anodizing bath process generated particles of the smallest average size (44.3 nm) and the lowest human lung-deposited surface area (1.2 µm 2 /cm 3 ). The total number of particles and the surface area can only be fairly correlated for environments in which the surface area presented higher values. The transmission electron microscopy analysis confirmed the presence of aluminum oxide particles of different dimensions near the LB and AB areas and polymeric-based particles near the LP areas. The findings of this study indicated that lacquering and anodizing surface treatments are indeed responsible for the emission of airborne nanoparticles. It also highlights the importance of control strategies as a means of protecting workers' health and environment.